SCHOOL STAKEHOLDERS’ LEVEL OF ENGAGEMENT AND PERFORMANCE ON MODULAR DISTANCE LEARNING - Bonifacio H. Rivera, Jr. (EPRA International Journal of Multidisciplinary Research (IJMR), 2023)
This study determined the relationship between the school stakeholders’ level of engagement and the level of school performance of Public Elementary Schools of Dolores District on Modular Distance Learning for the school year 2020-2021. A correlation research design was used to find the relationship between school stakeholders’ level of engagement and the level of school performance of Public Elementary Schools using an adopted survey questionnaire. A total of 462 respondents were utilized in the study to get the data required. The statistical tools used in the analysis of the data were frequency, percentage, mean, grand mean, Pearson r, and t-test. Based on the findings of the study, the level of engagement of stakeholders of public elementary schools in Dolores District during Modular Distance learning as perceived by internal and external stakeholders are very satisfactory. The school performance as assessed by teachers in terms of the school overall mean percentile scores are very satisfactory; school-based management level of implementation is developing; learning delivery modality implementation are very satisfactory; and learning continuity plan implementation obtain very satisfactory performance. There was a significant relationship between the level of School Stakeholders’ Engagement and the School performance of Public Elementary Schools in the Dolores district during modular distance learning. There is no significant difference between the internal and external stakeholders before and after the engagement. Based on the results of the study, there is a need for a national standard for the assessment and evaluation of school performance to determine significant issues, problems, gaps and needs to support and strengthen the competencies of school heads and teachers to enjoy their work and be satisfied in the new normal.